Bacillus sp. strains to produce bio-hydrogen from the organic fraction of municipal solid waste. (15th August 2016) - Shah, A.T.; Favaro, L.; Alibardi, L.; Cagnin, L.; Sandon, A.; Cossu, R.; Casella, S.; Basaglia, M.
Graphical abstract: Highlights: For the first time pure microbial cultures produced bio-hydrogen from organic waste. Two Bacillus sp. strains were selected for high amylolytic activities. The strains produced high H2 -yields from glucose and soluble starch. Promising H2 production was confirmed also from organic waste. Abstract: Bio-hydrogen, obtained by fermentation of organic residues, is considered a promising source of renewable energy. However, the industrial scale H2 production from organic waste is far to be realized as technical and economical limitations have still to be solved. Low H2 yields and lack of industrially robust microbes are the major limiting factors. To look for bacteria with both interesting hydrogen fermentative traits and proper robustness, granular sludge from a brewery full scale Upflow Anaerobic Sludge Blanket (UASB) digester was selected as trove of microbes processing complex substrates. One hundred and twenty bacterial strains, previously isolated from heat-treated granular sludge and genetically identified by 16S rDNA sequencing, were screened for extracellular hydrolytic enzymes on cellulose, hemicellulose, starch, pectin, lipids, protein. The most interesting hydrolytic strains were assessed for their H2 production from glucose and soluble starch. Two Bacillus sp. strains, namely F2.5 and F2.8, exhibited high H2 yields and were used as pure culture to convert Organic Fraction of Municipal Solid Waste (OFMSW) into hydrogen. The strains produced up to 61 mL of H2 per grams of volatile solids and could be considered as good candidates towards the development of industrially relevant H2 -producing inoculants. This is the first successful application of pure microbial cultures in bio-hydrogen production from OFMSW.